Concordance to the Greek New Testament - Moulton, W. F. (William Fiddian), 1835-1898.; Geden, A. S. (Alfred Shenington), 1857-1936.; Moulton, H. K. (Harold Keeling); Marshall, I. Howard. 1934- (London, UK ; New York : T. and T. Clark, 2002)
This edition is based on the Greek text in The Greek New Testament (4th edition) which is virtually identical to Novum Testamentum Graece (27th edition), the two most widely used editions of the Greek New Testament, giving rise to several thousand major and minor revisions. The most important features of earlier editions have been retained: for example, quotations are given with grammatical completeness as far as possible, the Hebrew text of direct quotations from the Old Testament is included, and references indicate whether vocabulary in the New Testament is also found in the classical Greek or in the Septuagint. - Publisher.
"A Continuum imprint".
Keywords: Bible. -- Concordances, Greek